-2(8+4x)=(8+3x)

Simple and best practice solution for -2(8+4x)=(8+3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(8+4x)=(8+3x) equation:


Simplifying
-2(8 + 4x) = (8 + 3x)
(8 * -2 + 4x * -2) = (8 + 3x)
(-16 + -8x) = (8 + 3x)

Remove parenthesis around (8 + 3x)
-16 + -8x = 8 + 3x

Solving
-16 + -8x = 8 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-16 + -8x + -3x = 8 + 3x + -3x

Combine like terms: -8x + -3x = -11x
-16 + -11x = 8 + 3x + -3x

Combine like terms: 3x + -3x = 0
-16 + -11x = 8 + 0
-16 + -11x = 8

Add '16' to each side of the equation.
-16 + 16 + -11x = 8 + 16

Combine like terms: -16 + 16 = 0
0 + -11x = 8 + 16
-11x = 8 + 16

Combine like terms: 8 + 16 = 24
-11x = 24

Divide each side by '-11'.
x = -2.181818182

Simplifying
x = -2.181818182

See similar equations:

| 2x^2-13x+27=0 | | m(6m+3)= | | 10x^2+35x-75=0 | | 4(7-5)= | | 3m+-6=9 | | S+4=-6 | | U=55(6)+217 | | U=55n+217 | | 12=0.75x+1.35x | | 23-5y=23+5y | | -50t^2+100t=0 | | 16x+48= | | 3(5x-1)=4(3x+6) | | 5m+4=3-4(m+2) | | 2x-1/2=4-3x | | 3t-8=4t+8 | | 4x+2x+3x+2=3(6) | | 2-m=5 | | n=-4n+25 | | -50t^2+100=0 | | 4x+2x+3x+2=18 | | (37/30-x):25/3=x:4 | | 3t-8=4(t-z) | | -50t+100t=0 | | U=14n+231+9n+9 | | 24(18-22)= | | 876x+23x+43+43=9000 | | X=16+8y | | 4y+2xy=0 | | 3.00=0.75b | | 2x-46=0 | | 0.5x+2.9=0.9x-0.3 |

Equations solver categories